(untitled) (Eurasian Scientific Herald, 2022)
Male infertility is a widespread disease among married couples. In almost 50% of cases, infertility is associated with a man, mainly due to a violation of spermatogenesis. Recently, the causes of male infertility have been increasing due to the progressive development of the environment and global changes. Psychological stress, general injuries, exposure to temperature and various chemicals, mobile phone, malnutrition, aging, hormonal imbalance play a crucial role in infertility in men. This review examines the features of the morphofunctional characteristics of the testes under the action of various factors affecting male fertility.